The organization of behavior : a neuropsychological theory - Hebb, D. O. (Donald Olding) (L. Erlbaum Associates, 2002)
An exploration of the organization of behaviour. Topics covered include: summation and learning in perception; field theory and equipotentiality; the first stage of perception - growth of the assembly; perception of a complex - the phase sequence; development of the learning capacity; and more.